Case report: De novo pathogenic variant in WFS1 causes Wolfram-like syndrome debuting with congenital bilateral deafness - Alías, Laura; López de Heredia, Miguel; Luna, Sabina; Clivillé, Núria; González-Quereda, Lídia; Gallano, Pía; de Juan, Júlia; Pujol, Albert; Diez, Santiago; Boronat, Susana; Orús, César; Lasa, Adriana; et al. (Frontiers in Genetics, 2022)
Background: Congenital deafness could be the first manifestation of a syndrome such as in Usher, Pendred, and Wolfram Syndromes. Therefore, a genetic study is crucial in this deficiency to significantly improve its diagnostic efficiency, to predict the prognosis, to select the most adequate treatment required and to anticipate the development of other associated clinical manifestations. Case presentation: We describe a young girl with a bilateral congenital profound deafness who initially received a single cochlear implant. Genetic study of her DNA by a custom-designed next-generation sequencing (NGS) panel detected a de novo pathogenic heterozygous variant in the WFS1 gene related to Wolfram-like syndrome, which is characterized by the presence of other symptoms such as optic atrophy. Due to this diagnosis, a second implant was placed after optic atrophy onset. The speech audiometric results obtained with both implants indicates that work successfully, allowing the patient to develop normal speech. No deterioration of the auditory nerves has been observed. Conclusions: The next-generation sequencing technique allows a precise molecular diagnosis of diseases with high genetic heterogeneity, such as hereditary deafness, when this was the only symptom presented by the patient at the time of analysis. The NGS panel, in which genes responsible for both syndromic and non-syndromic hereditary deafness were included, was essential to reach the diagnosis in such a young patient. Early detection of the pathogenic variant in the WFS1 gene allowed us to anticipate the natural evolution of the disease and to offer the most appropriate management to the patient.